Disentangling the complex photodynamics of mixed-linker Zr-MOFs – efficient energy and charge transfer processes. Issue 1 (8th December 2022) - Gutiérrez, Mario; Di Nunzio, Maria Rosaria; Caballero-Mancebo, Elena; Sánchez, Félix; Cohen, Boiko; Douhal, Abderrazzak
Abstract : Photodynamics of two mixed-linker Zr-MOFs showing different relaxation pathways including energy transfer, ligand-to-metal charge transfer, and long-lived charge separated states, which depends on the used modulators in the synthesis of the MOFs. Abstract : Controlling the composition, as well as the number and type of defects in metal–organic frameworks (MOFs) helps in the understanding of the interactions that govern their behaviours, and in consequence, their potential employment in a number of photonic applications. In this work, we report on the spectroscopy and photodynamics of two heterolinker (naphthalene-2, 6-dicarboxylic acid, NDC, and 4-amino-8-cyanonaphthalene-2, 6-dicarboxylic acid, NACDC) Zr-based MOFs that differ in the modulator used during the synthesis, thus leading to possible defects in the frameworks. We observed an inter-particle energy transfer (ET) that occurs from <10 to 160 ps in competition with an ultrafast intra-particle ET event from excited NDC to NACDC. In addition, due to the heterogeneity of the system, we found two different populations of the push–pull NACDC linker emitting from the charge transfer (CT) state. Single crystal fluorescence microscopy experiments further demostrated that the photobehavior of the studied MOFs is dominated by NACDC. Nanosecond (ns)-flash photolysis also revealed different photobehaviours related to the presence of defects, while the femtosecond (fs)-dynamics is independent of the modulators used for the MOFs' synthesis. These results may help in engineering of MOFs for their application in photon-based science and technology and may lead to the construction of optoelectronic devices and better photocatalysts based on these materials.